Self-prioritization with unisensory and multisensory stimuli in a matching task - Desebrock, C; Spence, C; Barutchu, A (Springer, 2022)
A shape-label matching task is commonly used to examine the self-advantage in motor reaction-time responses (the Self-Prioritization Effect; SPE). In the present study, auditory labels were introduced, and, for the first time, responses to unisensory auditory, unisensory visual, and multisensory object-label stimuli were compared across block-type (i.e., trials blocked by sensory modality type, and intermixed trials of unisensory and multisensory stimuli). Auditory stimulus intensity was presented at either 50 dB (Group 1) or 70 dB (Group 2). The participants in Group 2 also completed a multisensory detection task, making simple speeded motor responses to the shape and sound stimuli and their multisensory combinations. In the matching task, the SPE was diminished in intermixed trials, and in responses to the unisensory auditory stimuli as compared with the multisensory (visual shape+auditory label) stimuli. In contrast, the SPE did not differ in responses to the unisensory visual and multisensory (auditory object+visual label) stimuli. The matching task was associated with multisensory ‘costs’ rather than gains, but response times to self- versus stranger-associated stimuli were differentially affected by the type of multisensory stimulus (auditory object+visual label or visual shape+auditory label). The SPE was thus modulated both by block-type and the combination of object and label stimulus modalities. There was no SPE in the detection task. Taken together, these findings suggest that the SPE with unisensory and multisensory stimuli is modulated by both stimulus- and task-related parameters within the matching task. The SPE does not transfer to a significant motor speed gain when the self-associations are not task-relevant.